(3Pjd QaY GdCUQ Yf bVGI eUQs - (3TeS GdOjf CHi GdNjQ eMeO Hf YHO GdQMef Hf eMeO Hf CHi HcQ Hf YKeGf GdSNGhi GdTGaYjs; (3TgGH GdOjf CHh GdaVd CMeO Hf Ydj Hf MLQ GdYSbdGfi,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMce GdYOd , GdTGed cdkG ef Ndb HGdLhO s
(3QJHg ceG ai GdCUd Ydi GdMQha hgj fSNI eUhQI Yf fSNI ShgGLs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B138 s
Keywords: (3GdJGQjNs